Integrating the invisible fabric of nature into fisheries management - Travis, Joseph (2013)
Overfishing and environmental change have triggered many severe and unexpected consequences. As existing communities have collapsed, new ones have become established, fundamentally transforming ecosystems to those that are often less productive for fisheries, more prone to cycles of booms and busts, and thus less manageable. We contend that the failure of fisheries science and management to anticipate these transformations results from a lack of appreciation for the nature, strength, complexity, and outcome of species interactions. Ecologists have come to understand that networks of interacting species exhibit nonlinear dynamics and feedback loops that can produce sudden and unexpected shifts. We argue that fisheries science and management must follow this lead by developing a sharper focus on species interactions and how disrupting these interactions can push ecosystems in which fisheries are embedded past their tipping points.